Open‐source, low‐cost modular GPS collars for monitoring and tracking wildlife - Foley, CJ; Sillero-Zubiri, C (Wiley, 2020)
1. Monitoring the movements and behaviour of wildlife using radio telemetry or GPS devices has been critical to the fields of ecology and conservation over several decades. For many field projects however, commercially available devices can be expensive and may not always be ideally suited for collecting desired data.